CULTURAL OPPORTUNITIES IN CONSTANTINOPLE IN SELECTED TESTIMONIALS OF VENETIAN AND RUSSIAN DIPLOMATS (XVIII AND XIX CENTURIES) (Heritage, 2023)
It is well known that during the 18th and 19th centuries, European ideas and the presence of many foreign envoys in Constantinople enabled Europeans to get better acquainted with the flows of Ottoman culture and civilization. This was particularly striking during the period of reforms or Тanzimat that led to the modernization of education and the Europeanization of society in the Ottoman Empire. The mentioned reforms contributed to the separation from the previous traditional cultural values, and Constantinople, where many European diplomatic missions were located during that period, was an important diplomatic and cultural cosmopolitan center. There is a lot of valuable information about it recorded in the reports of European and other foreign envoys. Particularly valuable examples of such sources can be found in the letters and travelogues of Venetian envoys from the 18th century, as well as Russian envoys from the 19th century, which is why they present valuable testimonies within the framework of cultural history.
Keywords: /